University-community partnerships for promoting social responsibility in higher education - Sengupta, Enakshi; Blessinger, Patrick; Mahoney, Craig (Innovations in higher education teaching and learning, 2020)
The role of universities is not only restricted to knowledge exchange, higher education institutions also play a leading role in the development of society, and should engage as active members of their local communities. This book provides empirical evidence on how some universities have shifted social responsibility to be one of their primary focuses, and have engaged with society to enhance their values. The authors present international case studies, from Indonesia to the UK, that examine community engagement, inequality, university-corporate partnerships, philanthropy, and sustainable futures, among other important topics.--Publisher's website.